Reproductive performance of Arab mares in the Kingdom of Saudi Arabia - Ali, A.; Alamaary, M.; Al-Sobayil, F. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2014)
Objective: The aim of this study was to evaluate the reproductive performance of the Arab mares in the Kingdom of Saudi Arabia (KSA). Methods: Managers of 26 studfarms containing 1014 Arab mares at five districts were asked to complete a questionnaire on the reproductive efficiency of their mares. Results: The mean age at first mating was 3.06 ± 0.5 years. Mares were mated equally in winter and all over the year. Natural mating was mostly used (76.9%). The means of estrus duration and estrus interval were 6.58 ± 1 days and 19.57 ± 1.8 days, respectively. The means of first service and overall pregnancy rates and the number of cycles/pregnancy were 52.71 ± 20.2%, 83.72 ± 15.0%, and 1.46 ± 0.3, respectively, with no effect of the postpartum interval, district, or season. The average pregnancy duration was 335.5 ± 10.2 days. It was shorter in mares mated by day 9 postpartum than in those mated later (p < 0.05). The ratio of stallion/mares ranged from 1:4 to 1:24, with no correlation with the pregnancy rates or the number of cycles/pregnancy. Discussion: Photoperiodic regulation and changes in the hypothalamichypophyseal axis of mares are usually associated with the seasonal reproductive activity of mares in the temperate but not in subtropical areas. Short duration of gestation for mares mated by day 9 after foaling may be related to the nutritional status of dams. Conclusion: The obtained data represent the first record of the reproductive performance of Arab mares in the KSA, which could be used to anticipate their performance under different managements. Clinical relevance: The Arab mares in the KSA are not seasonal and can reproduce efficiently all over the year. District and season did not influence the fertility.
Keywords: Reproduction; horse; pregnancy rate; pregnancy duration